Quantitative Comparative Proteomics Reveal Biomarkers for Dengue Disease Severity - Han, Lifen; Ao, Xiulan; Lin, Shujin; Guan, Shengcan; Zheng, Lin; Han, Xiao; Ye, Hanhui (Frontiers in Microbiology, 2019)
Dengue fever (DF) could develop into dengue haemorrhagic fever (DHF) with increased mortality rate. Since the clinical characteristics and pathogen are same in DF and DHF. It’s important to identify different molecular biomarkers between DF and DHF patients. We conducted a clinical plasma proteomics study using quantification (TMT)-based quantitative proteomics methodology to found the differential expressed protein in DHF, DF and healthy-control. In total 441 proteins were identified up or down regulated in DF or DHF plasma. There proteins are enriched in diverse biological processes such as proteasome pathway, Alanine, aspartate, and glutamate metabolism and arginine biosynthesis. Several proteins such as PLAT, LAMB2 and F9 were upregulated in only DHF cases, not in DF, compared with healthy-control. In another way, FGL1, MFAP4, GLUL and VCAM1 were upregulated in both DHF and DF cases compare with healthy-control. RT-PCR and ELISA were used to validate these upregulated gene expression and protein level in 54 individuals. Results displayed the same pattern as proteomics analysis. These new founding identified potential molecular biomarkers for future development in precision diagnostic to DF and DHF.